Respon Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) terhadap Pemberian Paklobutrazol - Diah Karunia Binawati; Ngadiani Ngadiani (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to examine the response of cayenne pepper plants to the treatment of paklobutrazole with various concentrations. This study used a completely randomized design (CRD) with 6 treatment concentrations of paklobutrazole, namely: 0 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm, with 4 repetitions. The parameters observed were: plant height, flowering time, and the number of flowers of chili plants. Data analysis used Analysis of Variance (ANOVA) according to the experimental design at a significance of 0.5. The follow-up test used the BNT test at a level of 0.05 if there was a significant effect. The results showed that the administration of paclobutrazole with a concentration of 500 ppm gave a better effect on plant height, flowering time, and number of leaves compared to other treatments.